Construction of personal knowledge maps for a peer-to-peer information-sharing environment. Issue 3 (1st June 2018) - Qin, Chunxiu; Zhao, Pengwei; Mou, Jian; Zhang, Jin
Abstract : Purpose: Browsing knowledge documents in a peer-to-peer (P2P) environment is difficult because knowledge documents in such an environment are large in quantity and distributed over different peers who organize the documents according to their own views. This paper aims to propose a method for constructing a personal knowledge map for a peer to facilitate knowledge browsing and alleviate information overload in P2P environments. Design/methodology/approach: The research presents a method for constructing a personal knowledge map. The method adopts an ontology-concept-tree-based classification algorithm to recognize a peer's personal knowledge structure and construct a personal knowledge map, and uses a self-organizing map algorithm to cluster and visualize the knowledge documents. The correctness of the created knowledge map is evaluated with a collection of abstracts of academic papers. Findings: The method for constructing a personal knowledge map is the main finding of this research. The evaluation shows that the created knowledge map is good in quality. Research limitations/implications: The proposed method provides a way for P2P platforms to understand their users' knowledge background, as well as to improve the P2P platform environment. However, the proposed method will not help a peer when he has nothing in his individual knowledge document repository (i.e. the "cold start" problem). The method also requires a relatively good ontology base for a P2P document sharing system to use the method effectively. Originality/value: It is novel that the proposed method organizes the knowledge documents related to a peer's knowledge background into a personal knowledge map. Moreover, the created knowledge map combines the advantages of a hierarchical display and a map display. It has values for a distributed P2P environment to facilitate users' knowledge browsing and to alleviate information overload.